2003
DOI: 10.1002/chin.200327137
|View full text |Cite
|
Sign up to set email alerts
|

Silica Sulfuric Acid: An Efficient and Reusable Catalyst for the One‐Pot Synthesis of 3,4‐Dihydropyrimidin‐2(1H)‐ones.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…hCA II, the dominant physiologic isoform 90,91 , was potently inhibited by all newly synthesised N-alkyl (aril)-tetra pyrimidine thiones (1-5) with K i s in the range of 181.8 ± 41.9-273.6 ± 41.4 p.m. Also, similar to hCA I, the most powerful hCA II inhibition property was shown by allyl 6-methyl-2-thioxo-4-(p-tolyl)-1,2,3,4-tetrahydropyrimidine-5-carboxylate (1) with K i value of 155.4 ± 25.9 p.m. Also, AZA, which was used as clinical CA inhibitor, showed a K i value of 271.8 ± 54.5 p.m. This result clearly showed that all newly synthesised N-alkyl (aril)-tetra pyrimidine thiones (1)(2)(3)(4)(5) .…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…hCA II, the dominant physiologic isoform 90,91 , was potently inhibited by all newly synthesised N-alkyl (aril)-tetra pyrimidine thiones (1-5) with K i s in the range of 181.8 ± 41.9-273.6 ± 41.4 p.m. Also, similar to hCA I, the most powerful hCA II inhibition property was shown by allyl 6-methyl-2-thioxo-4-(p-tolyl)-1,2,3,4-tetrahydropyrimidine-5-carboxylate (1) with K i value of 155.4 ± 25.9 p.m. Also, AZA, which was used as clinical CA inhibitor, showed a K i value of 271.8 ± 54.5 p.m. This result clearly showed that all newly synthesised N-alkyl (aril)-tetra pyrimidine thiones (1)(2)(3)(4)(5) .…”
Section: Resultsmentioning
confidence: 74%
“…Many types of CAIs have been reported recently, together with their potential applications 27,28 . Some newly synthesised N-alkyl (aril)-tetra pyrimidine thiones (1)(2)(3)(4)(5) were screened for the inhibition of both human CA isoforms involved in important physiologic or pathologic processes, i.e. the cytosolic, hCA I, and II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of BF 3 .OEt 2 [44], polyphosphate ester [45], (NH 4 ) 2 CO 3 [46], NaCl [47] and {Fe 2 CuO} clusters [48] has also been described. The Biginelli reaction can strongly be accelerated by various procedures including heteropoly acids [49], silica sulfuric acid [50] and ferric chloride/tetraethyl orthosilicate [51].…”
Section: Introductionmentioning
confidence: 99%
“…For this particular Biginelli 25 as promoters for this Biginelli reaction. While in the original Biginelli protocol EtOH was used as protic solvent 10,13,23 , suitable alternative solvents are MeCN 16,18,[20][21]25 and tetrahydrofuran (THF) 14 . With respect to environment-friendly procedures, several groups have developed solvent-free synthesis of monastrol 3,15,17,19,22,24 .…”
Section: Introductionmentioning
confidence: 99%